Scaling formation and mitigation during electrodialysis for desalination and nutrient recovery - Liu, Hong (Nanyang Technological University, 2024)
Electrodialysis (ED) stands as a promising and versatile separation technology, flexible to customization for diverse applications such as desalination, nutrient recovery, wastewater treatment, energy generation, and so on. Despite its wide-ranging utility, ED is not devoid of challenges. In particular, the formation of scaling emerges as an obstacle, significantly impacting the performance of ED. Addressing this concern constitutes a key area of focus for future advancements in this field.